Analysis of Genetic Determination of Vibrio cholerae Tweenase Activity - A. B. Mazrukho; E. V. Monakhova; O. V. Duvanova; B. N. Mishan’Kin; V. D. Kruglikov (Проблемы особо опасных инфекций, 2012)
Studied are Vibrio cholerae of different serogroups on the presence of cef (CHO cell elongating factor) gene and activity against tweens and tributyrin using HDS-agar, prepared on the basis of bakery yeast pancreatic digest. Determined is the fact that all cef-positive strains hydrolyze tweens 20, 40, 60, 80, 85 and all but toxigenic V.cholerae O139, hydrolyze tributyrin. In contrast, non-toxigenic cef-negative strains of O139 serogroup, are active only against the latter. Apparently, the tweenase activity of Vibrio cholerae is provided, partly, by Cef, and the ability to hydrolyze tributyrin is the result of combined activity of Cef and other ferments. Shown is the efficiency of HDS-agar application to determine these characteristics.